A catechism for business : tough ethical questions & insights from Catholic teaching - Abela, Andrew V., 1965-; Capizzi, Joseph E. (The Catholic University of America Press, 2021)
"In the four years since the publication of the second edition of A Catechism for Business, Pope Francis' enormous contributions to spreading the good news of the gospel has led to his promulgation of two apostolic exhortations and now a new encyclical, Fratelli tutti, focusing on human fraternity and solidarity. The vibrant tradition of Catholic thinking on social issues is unparalleled in its capacity to help guide human beings towards individual and communal flourishing. The context of a world emerging from a pandemic and new challenges to Christian faith and practice beckon for a refreshed look at pressing questions. Editors Andrew Abela and Joseph Capizzi offer the updated third edition which will incorporate material from both of these apostolic exhortations and the new encyclical."--